2005
DOI: 10.1016/j.destud.2004.08.001
|View full text |Cite
|
Sign up to set email alerts
|

The bodily basis of product experience

Abstract: Based on the work of Lakoff and Johnson, this paper argues that part of our product experience is rooted in bodily interactions between people and their environments. Lakoff and Johnson convincingly demonstrated that repeated bodily interactions of a similar kind lead to the formation of image schemas guiding our understanding of verbal expressions. Here, it is proposed that the same underlying principles also govern our understanding of the expression of products. If correct, product expressions theoretically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 4 publications
0
14
0
Order By: Relevance
“…With respect to impressions of intensity or potency perceptions, various shape features (e.g., size, relative height, shape angularity) have been shown to affect consumer evaluations (e.g., Arnheim, 1974;Van Rompay, Hekkert, & Muller, 2005;Van Rompay, Hekkert, Saakes, & Russo, 2005;Zhang, Feick, & Price, 2006). The relationship between shape angularity and potency perceptions has been particularly well documented.…”
Section: Product Shape and Potency Perceptionsmentioning
confidence: 96%
“…With respect to impressions of intensity or potency perceptions, various shape features (e.g., size, relative height, shape angularity) have been shown to affect consumer evaluations (e.g., Arnheim, 1974;Van Rompay, Hekkert, & Muller, 2005;Van Rompay, Hekkert, Saakes, & Russo, 2005;Zhang, Feick, & Price, 2006). The relationship between shape angularity and potency perceptions has been particularly well documented.…”
Section: Product Shape and Potency Perceptionsmentioning
confidence: 96%
“…Along these lines, Van Rompay, Hekkert, and M€ uller (2005) showed that our embodied image schemas could explain our interpretation of objects' abstract characteristics, such as trustworthiness, dominance, restlessness, and so forth. For instance, they found that jugs that express higher degrees of closure of their contents were perceived as more 'secure' and 'constricting'.…”
Section: Embodied Vs Learned Metaphorsmentioning
confidence: 98%
“…The phrase "embodied design" was first coined by Thomas van Rompay, then a cognitive-psychologist-turned-industrial-designer, who used Conceptual Metaphor Theory to tune the emotional experience evoked by public structures, such as bus-stop shelters (Van Rompay, Hekkert, & Muller, 2005). Abrahamson (2009) imported the phrase into the learning sciences to describe the craft of engineering pedagogical artifacts and activities attuned to how humans naturally perceive the world, yet conducive to disciplinary reanalysis and signification.…”
Section: Embodied Design: From Theory To Practicementioning
confidence: 99%